Cordyceps militaris solid medium extract alleviates lipopolysaccharide-induced acute lung injury via regulating gut microbiota and metabolism - Wang, Xiaoya; Zhang, Kang; Zhang, Jingyan; Xu, Guowei; Guo, Zhiting; Lu, Xiaorong; Liang, Chunhua; Gu, Xueyan; Huang, Liping; Liu, Shuqi; Wang, Lei; Li, Jianxi (Frontiers in Immunology, 2025)
Acute lung injury (ALI) is a common respiratory disease, Cordycepin has been reported to reduce ALI, which is an effective component in Cordyceps militaris solid medium extract (CMME). Therefore, we aimed to explore the alleviating effect and mechanism of CMME on ALI. This study evaluated the effect of CMME on lipopolysaccharide (LPS)-induced ALI mice by analyzing intestinal flora and metabolomics to explore its potential mechanism. We assessed pulmonary changes, inflammation, oxidative stress, and macrophage and neutrophil activation levels, then we analyzed the gut microbiota through 16S rRNA and analyzed metabolomics profile by UPLC-QTOF/MS. The results showed that CMME treatment improved pulmonary injury, reduced inflammatory factors and oxidative stress levels, and decreased macrophage activation and neutrophil recruitment. The 16S rRNA results revealed that CMME significantly increased gut microbiota richness and diversity and reduced the abundance of Bacteroides compared with Mod group significantly. Metabolic analysis indicated that CMME reversed the levels of differential metabolites and may ameliorate lung injury through purine metabolism, nucleotide metabolism, and bile acid (BA) metabolism, and CMME did reverse the changes of BA metabolites in ALI mice, and BA metabolites were associated with inflammatory factors and intestinal flora. Therefore, CMME may improve lung injury by regulating intestinal flora and correcting metabolic disorders, providing new insights into its mechanism of action.